Mewujudkan Bantuan Hukum Bagi Terdakwa Kasus Narkotika di Rumah Tahanan Negara Kelas IIb Boyolali - Kurnianingsih, Marisa; Iksan, Muchamad; Wibisono, Fiqkri Akbar; Anastasya, Dita Nadya; Moestofa, Yoesoef (CV. Edutechnium Indonesia, 2024)
This legal counseling aims to understand the preparation and implementation process carried out by legal advisors from BKBH, Universitas Muhammadiyah Surakarta. Before trial assistance, there is a preparation process that includes the defendant's rights, which are fundamental principles in the legal system. These principles aim to protect the defendant's human rights and ensure that the judicial process runs fairly. Several rights of the defendant, generally recognized and guaranteed by various legal systems, including criminal law, are the right to legal assistance, the right to a prompt trial, the right to present witnesses, the right not to bear the burden of evidence, the right to a public trial, and the right to assistance from an interpreter if they do not understand the Indonesian language. The process and stages of trial assistance for narcotics abuse cases involving prison inmates at Class IIB Boyolali State Detention Center, who are about to or are currently being tried in Boyolali District Court, go through several steps. These begin with the reading of the indictment and conclude with the final verdict. The trial stage is crucial in the criminal justice process, where all evidence will be examined publicly. This community assistance provides education related to the defendant's rights in narcotics cases at Boyolali District Court and emphasizes the importance of the legal advisor's role in ensuring that the defendant's rights are fulfilled during the trial process.